2019
DOI: 10.1002/pad.1866
|View full text |Cite
|
Sign up to set email alerts
|

Reluctant policy innovation through profit concession and informality tolerance: A strategic relational view of policy entrepreneurship in China's urban redevelopment

Abstract: Summary This paper engages with the theoretical perspective of policy entrepreneurship to examine the pattern and process of policy change in the context of China's urban redevelopment. Drawing upon a strategic‐relational reinterpretation of policy entrepreneurship, this paper identifies a distinctive form of reluctant policy innovation in the “three old renewals” scheme initiated in Guangzhou where profit concession and informality tolerance were practiced to create a small window of opportunity for the proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Adopting a strong SE allows firms to create, discover and exploit new opportunities and to capture value from doing so. The impact of SE on EOR is consistent with a few studies (Boudreaux, 2020;Hu et al, 2020). Likewise, this study found that EOR has a significant effect on BG.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adopting a strong SE allows firms to create, discover and exploit new opportunities and to capture value from doing so. The impact of SE on EOR is consistent with a few studies (Boudreaux, 2020;Hu et al, 2020). Likewise, this study found that EOR has a significant effect on BG.…”
Section: Discussionsupporting
confidence: 92%
“…The relationship between strategic entrepreneurship and entrepreneurial opportunity recognition A growing number of scholars have noted that SE is positively linked to EOR (Boudreaux, 2020;Hu et al, 2020). Altindag et al (2011) suggest that once SE is present, firms use entrepreneurial strategic actions to identify opportunities.…”
Section: Business Growthmentioning
confidence: 99%
“…Policymaking is not necessarily a functional process of formulating solutions for meeting domestic needs but a result of policy learning (Dolowitz & Marsh, 2000;Jarvis & He, 2020;Hall, 1993). Ebbs and flows of the trends of economic policies, be it the Keynesian welfare state, state-centered developmentalism, or neoliberalism, can be contingent on the policy actors (Hu et al, 2020). Nevertheless, especially in a catch-up economy, rational policy actors, who calculate not only the technical efficiency of a policy instrument but also political effectiveness, may utilize these trends in "advanced economies" to advocate their policy alternative (Chindarkar et al, 2017;Evans, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The 'economic achievement is only one of many considerations in career advancement' (Wu, 2018(Wu, , p.1385 as local politics also shows significant concern for maintaining state power. This transformation of state-market-society interaction in urban redevelopment is argued to be a policy concession made by the state to mitigate social conflicts (Hu et al, 2020). Public participation is encouraged to legitimate redevelopment and help the implementation of redevelopment project.…”
Section: Introductionmentioning
confidence: 99%